ARAHAN PEMBANGUNAN BERBASIS MITIGASI COVID-19 RW I KELURAHAN KRAMAS, KOTA SEMARANG - Crismon Alfajri Agus Pratama (PT. Banjarese Pacific Indonesia, 2024)
The Covid-19 pandemic has had various impacts on regional and urban developments. This phenomenon affects the planning and development process, forcing a correction in development planning in Indonesia. Development planning can be started within the scope of small area given that the concept of development in Indonesia refers to development from below and from above. RW I Kelurahan Kramas is one of the areas affected by the Covid-19 pandemic so it requires mitigation of development planning within the scope of an area oriented towards social disaster mitigation. This community development activity aims to produce planning documents that are oriented towards social disaster mitigation but still consider the sustainability aspects of an area and can serve as a guide for policy makers in formulating development programs in RW I Kelurahan Kramas. This planning document formulating uses a Rational Comprehensive Planning (RCP) analysis method by conducting a comprehensive analysis of the conditions of an area. The data collection method used in this service was through interviews and secondary data search. The results obtained in this analysis are 6 groups of development directions, namely improving the quality of infrastructure, improving health and safety, building layout, improving environmental quality, increasing the economy and improving the aesthetics of the area.